PENGARUH PROGRAM PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN HOTEL BERBINTANG DI BALI: MOTIVASI KERJA SEBAGAI VARIABEL PEMEDIASI - I Gusti Ayu Putu Wita Indrayani (JURNAL KEPARIWISATAAN, 2017)
The research was conducted by taking sampling of 39 hotels spread across North Bali (Jembrana), East Bali (Kintamani), South Bali (Nusa Dua, Kuta, Legian), West Bali (Singaraja), and Central Bali (Ubud). This study aims to identify the mediation role of work motivation on the relationship of career development and employee performance of star hotels in Bali. To achieve this objective, this study used survey design to collect data from 139 respondents. The research hypothesis test used multiple linear regression analysis with Statistical Package for Social Science (SPSS) 22 for Windows. To test the mediation effect the causal step method was applied in the Multiple Regression Analysis method. The results showed thatthere is significant influence among latent variables. Career development has a positive and significant impact on work motivation and employee performance. Work motivation also proved to have a positive and significant impact on employee performance. In addition, work motivation, which is mediation variable between career development and employee performance, indicates partial mediation. In general, these results are consistent with previous studies.